Big Data Analytics and Knowledge Discovery: 21st International Conference, DaWaK 2019, Linz, Austria, August 26-29, 2019, Proceedings - International Conference on Data Warehousing and Knowledge Discovery; Ordonez, Carlos (Computer scientist); Song, Il-Yeol; Anderst-Kotsis, Gabriele; Tjoa, A Min; Khalil, Ismail (LNCS sublibrary. SL 3, Information systems and applications, incl. Internet/Web, and HCI, 2019)
This book constitutes the refereed proceedings of the 21st International Conference on Big Data Analytics and Knowledge Discovery, DaWaK 2019, held in Linz, Austria, in September 2019.The 12 full papers and 10 short papers presented were carefully reviewed and selected from 61 submissions. The papers are organized in the following topical sections: Applications; patterns; RDF and streams; big data systems; graphs and machine learning; databases.